Tobacco use prevalence and its determinate factor in Ethiopia- finding of the 2016 Ethiopian GATS - Sisay Derso Mengesha; Kirubel Tesfaye Teklu; Abel Weldetinsae; Melaku Gizaw Serte; Moa Abate Kenea; Daniel Abera Dinssa; Mesay Getachew Woldegabriel; Tsigereda Assefa Alemayehu; Wassihun Melaku Belay (BMC, 2022)
Abstract Background Tobacco, one of the risk factors for non-communicable diseases, kills 8 million people each year. Like other sub-Saharan countries, Ethiopia faces the potential challenge of a tobacco epidemic. However, there is no organized data on the prevalence of tobacco use in the country. Therefore, this study aims to determine adult tobacco use in Ethiopia. Methods The study was conducted using the WHO and CDC GATS survey methods. Complex survey analysis was used to obtain prevalence and population estimates with 95% confidence intervals. Bivariate regression analyses were employed to examine factors related to tobacco use. Results The overall tobacco use percentage was 5.0% [95% CI (3.5, 6.9)], of which 65.8% [95% CI (53.4, 76.3)] only smoked tobacco products; 22.5% [95% CI (15.7, 31.2)] used smokeless tobacco only; and 11.8% [95% CI (6.5, 20.4)] used both smoked and smokeless tobacco products. In 2016, more men adults (8.1%) used tobacco than women did (1.8%). Eight out of eleven states have a higher smoking rate than the national average (3.7%). Gender, employment, age, religion, and marital status are closely linked to current tobacco use (p-value< 0.05). Men adults who are employed, married, and mostly from Muslim society are more likely to use tobacco. Conclusion The prevalence of tobacco use is still low in Ethiopia. However, the percentage of female smokers is increasing, and regional governments such as Afar and Gambella have a relatively high prevalence. This calls for the full implementation of tobacco control laws following the WHO MPOWER packages. A tailored tobacco control intervention targeting women, younger age groups, and regions with a high proportion of tobacco use are recommended.